2015
DOI: 10.1186/s40001-015-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Better short-term efficacy of treating severe flail chest with internal fixation surgery compared with conservative treatments

Abstract: BackgroundThe objective of the study is to provide evidence for selecting the best treatment approach for severe flail chest by comparing surgical and conservative treatments.MethodsThis is a retrospective study in which 32 patients with severe flail chest were treated in the Fujian Provincial Hospital (China) between July 2007 and July 2012 with surgical internal rib fixation (n = 17) or conservative treatments (n = 15). Mechanical ventilation time, intensive care unit (ICU) stay time, pulmonary infection, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
(26 reference statements)
1
23
1
1
Order By: Relevance
“…The most recent publication about FC management by Xu et al found a shorter duration of mechanical ventilation and ICU stay when using operative management, supporting our findings [2]. Pneumonia rate was also significantly lower in their operative management group, but tracheostomy rate did not differ between both groups in the publication by Xu et al [2]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most recent publication about FC management by Xu et al found a shorter duration of mechanical ventilation and ICU stay when using operative management, supporting our findings [2]. Pneumonia rate was also significantly lower in their operative management group, but tracheostomy rate did not differ between both groups in the publication by Xu et al [2]. …”
Section: Discussionsupporting
confidence: 89%
“…“Flail chest occurs when three or more adjacent ribs are fractured in at least two places, creating a chest wall segment that moves paradoxically from the chest wall [2]. ” The paradoxical movements make breathing less efficient, resulting in poor oxygenation of blood and potential asphyxia [3].…”
Section: Introductionmentioning
confidence: 99%
“…They found that patients in the surgical group had shorter total mechanical ventilation time, decreased ICU stay, and decreased pulmonary infection rate. 8 Conversely, Naidoo et al evaluated 293 flail chest patients and found a non-significant benefit to conservative management, however, this study suffered from some relatively significant limitations, including retrospective design and lack of case controls. 6 Additional studies by Granhed & Pazooki, Zhang et.…”
Section: Related Literaturementioning
confidence: 91%
“…A special phenomenon called flail chest sometimes occurs when multiple rib fractures happen. Flail chest refers to the fracture of 3 or more than 3 ribs in adjacent parts at one side or two sides of the chest, leading to destruction of the thorax stability, softening of chest wall, and thus the paradoxical respiratory movement [2][3]. It often causes the lowering of respiratory efficiency of patients, then expiratory dyspnea, hypoxemia, and even respiratory distress syndrome, threatening the life of patients.…”
Section: Introductionmentioning
confidence: 99%